对比语言视角下汉柬语“饮食类”动词研究 - KOK MENG SEAK (Sinolingua: Journal of Chinese Studies, 2026)
From a syntactic perspective, both Chinese and Khmer are typical subject-verb-object (SVO) languages, and thus their linguistic features often exhibit a degree of symmetry. However, this study conducts a comparative analysis of the usage of "eat" and "drink" in Chinese and Khmer, revealing that despite their shared SVO structure, there are notable differences in verb-object constructions. In Chinese, the verb "eat" (chī) tends to select objects based on the physical form of food and has a broad range of applications, whereas in Khmer, "eat" (nham) encompasses the consumption of all types of food without emphasizing physical form, and its "drink" (phīrk) is strictly limited to beverages. Additionally, the expression of "eat" in Khmer varies depending on the listener’s seniority or social status, reflecting the language’s politeness culture. Nevertheless, the semantic scope of "eat" and "drink" in Khmer remains confined to food-related contexts, exhibiting less flexibility compared to Chinese. These differences often lead to errors among learners, particularly in mastering verb-object collocations. To address this, targeted teaching strategies—such as comparative explanations and contextual practice—should be employed to help students understand the distinctions and similarities in the usage of "eat" and "drink" between the two languages, thereby improving learning outcomes and providing practical support for cross-linguistic comparative studies.